Organizing modernity : new Weberian perspectives on work, organization, and society - Ray, Larry J.; Reed, M. I. (Michael I.) (Routledge, 1994)
This book provides a re-evaluation of Weber's work on the current debates about the institutional and organizational dynamics of modernity, offering interpretations of his work which emphasize the reality of modernity as a dual process.
Keywords: Weber, Max, -- 1864-1920.; Weber, Max, -- 1864-1920; Organizational sociology.; Sociologie des organisations.; BUSINESS & ECONOMICS -- Negotiating.; Organizational sociology; Organisational behaviour